Stress-related transcriptomic changes associated with GFP transgene expression and active transgene silencing in plants - Paraskevi Kallemi; Frederic Verret; Christos Andronis; Nikolaos Ioannidis; Nikolaos Glampedakis; Kiriakos Kotzabasis; Kriton Kalantidis (Scientific Reports, 2024)
Abstract Plants respond to biotic and abiotic stress by activating and interacting with multiple defense pathways, allowing for an efficient global defense response. RNA silencing is a conserved mechanism of regulation of gene expression directed by small RNAs important in acquired plant immunity and especially virus and transgene repression. Several RNA silencing pathways in plants are crucial to control developmental processes and provide protection against abiotic and biotic stresses as well as invasive nucleic acids such as viruses and transposable elements. Various notable studies have shed light on the genes, small RNAs, and mechanisms involved in plant RNA silencing. However, published research on the potential interactions between RNA silencing and other plant stress responses is limited. In the present study, we tested the hypothesis that spreading and maintenance of systemic post-transcriptional gene silencing (PTGS) of a GFP transgene are associated with transcriptional changes that pertain to non-RNA silencing-based stress responses. To this end, we analyzed the structure and function of the photosynthetic apparatus and conducted whole transcriptome analysis in a transgenic line of Nicotiana benthamiana that spontaneously initiates transgene silencing, at different stages of systemic GFP-PTGS. In vivo analysis of chlorophyll a fluorescence yield and expression levels of key photosynthetic genes indicates that photosynthetic activity remains unaffected by systemic GFP-PTGS. However, transcriptomic analysis reveals that spreading and maintenance of GFP-PTGS are associated with transcriptional reprogramming of genes that are involved in abiotic stress responses and pattern- or effector-triggered immunity-based stress responses. These findings suggest that systemic PTGS may affect non-RNA-silencing-based defense pathways in N. benthamiana, providing new insights into the complex interplay between different plant stress responses.